Motivación cognitiva del lenguaje y las formas de pensar: un análisis semiótico-cognitivo del sociolecto de la pandemia - Loayza Maturrano, Edward Faustino (2022)
The research approaches from a semiotic-cognitive approach the analysis of the phraseological repertoirethat emerged in the period of the SARS-CoV-2 pandemic since the months of March and April in Peruvian society. The objective of this study is to propose a model of semiotic-cognitive analysis applied to any sociolect from a transversal perspective. The proposed model is based on cognitive linguistics and symbolic interactionism. Information was collected through the newspapers of the written press in Metropolitan Lima. The analysis allowed to establish that eight ways of thinking or conceptual procedures are evidenced in the cognitive processes of language. The research allows us to conclude that the sociolect generated by COVID-19 in Peruvian society, according to the cognitive perspective, represent symbolic units motivated through linguistic-cognitive processes of a metaphorical, metonymic and hyperbolic type.